Decreased vitamin D increase the risk for subclinical hypothyroidism in individuals with T2DM: a cross-sectional study - Fang, Yaling; Wen, Xin; You, Hui; Huang, Yueye; Qu, Shen; Wang, Xingchun; Bu, Le (Frontiers in Nutrition, 2025)
BackgroundVitamin D is crucial for regulating calcium and phosphorus metabolism. More studies have revealed its role in chronic diseases. Our study aimed to examine the relationship between thyroid function and Type 2 Diabetes Mellitus (T2DM).Methods730 patients with T2DM were enrolled in this cross-sectional study. Among them, 118 subjects were classified as obese, while 613 were classified as non-obese. Thyroid and 25 hydroxyvitamin D(25(OH)D) levels were measured. Patients were categorized into lower and higher VD groups based on the median. Thyroid function was compared between groups and their association was analyzed.ResultsBody mass index (BMI), total cholesterol (TCH), triglyceride (TG), and free fatty acid (FFA) were significantly lower in the higher VD group compared to the lower VD group (all p < 0.05). In the higher VD group, free triiodothyronine (FT3) levels were significantly elevated (4.45 ± 0.93 vs. 4.95 ± 1.52 ng/mL, p < 0.001), while total triiodothyronine (TT4) (104.84 ± 21.17 vs. 99.99 ± 23.64 ng/mL, p = 0.008) and thyroid stimulating hormone (TSH) (2.88 ± 7.03 vs. 2.06 ± 1.72 ng/mL, p = 0.046) levels were significantly reduced compared to the lower VD group. VD showed a significant negative correlation with BMI, Glycosylated Hemoglobin (HbA1C), low-density lipoprotein (LDL-C), and FFA (r = −0.093, p = 0.016; r = −0.082, p = 0.036; r = −0.099, p = 0.011; r = −0.125, p = 0.001). FT3 and FT4 showed significant positive correlations with VD (r = 0.248, p < 0.001; r = 0.086, p = 0.025), while TT4 and TSH exhibited significant negative correlations (r = −0.103, p = 0.011; r = −0.080, p = 0.033). After adjusting for height, BMI, HGB, TCH, TG, FFA, and LDL, FT3 and FT4 remained significantly positively associated with VD (r = 0.227, p < 0.001; r = 0.089, p = 0.030), while TT4 and TSH continued to show significant negative associations (r = 0.091, p = 0.033; r = −0.081, p = 0.049). Linear regression analysis revealed a significant positive association between VD and FT3 (β = 4.144, p < 0.001) and negative associations with TT4 (β = −0.167, p < 0.001) and TSH (β = −0.412, p = 0.020). Logistic regression analysis indicated that VD serves as a protective factor against subclinical hypothyroidism (SCH) (OR 0.987, 95% CI 0.974–0.999, p = 0.035), even after adjusting for BMI, FBG, FINS, TCH, and HDL (OR 0.986, 95% CI 0.974–0.999, p = 0.041). T2DM patients with SCH had lower 25(OH)D levels compared to those without SCH (46.45 ± 4.76 vs. 45.40 ± 5.84 ng/mL, p = 0.029).ConclusionThese results suggest a dual relationship between VD and thyroid function. T2DM patients with SCH exhibited reduced VD levels.